Analisis Perencanaan Strategis Sistem Informasi Wisata Alam Curug Gomblang Mempergunakan Ward And Peppard - Titik Khawa Abdul Rahman; Nur Ayu Safitri; Naufal Oktafiano; Yerico Alexander (Telkom University, 2026)
Curug Gomblang Tourism in Banyumas Regency is a natural tourism destination with great potential as a leading regional attraction. However, its management is not yet supported by a structured information system strategy, thus limiting the effectiveness of digital promotion, service quality, and data-based decision-making capabilities. This study aims to develop a strategic information system plan for Curug Gomblang Tourism using the Ward and Peppard approach. The research method is descriptive-qualitative through field observations, interviews, digital documentation, and literature studies. Analysis is conducted on the four main components of the Ward and Peppard model, namely the internal business environment, the external business environment, the internal IS/IT environment, and the external IS/IT environment. The results show that Curug Gomblang faces a number of internal weaknesses, including the absence of a website, a manual ticketing system, limited IT competency, and unstructured visitor data documentation. Meanwhile, the external environment provides significant opportunities, such as the trend of natural tourism, the increasing use of social media, and the government's encouragement of digitalization of tourist villages. Through SWOT, value chain, and GAP analyses, an IS/IT strategy was formulated, including the development of an official website, the implementation of QR code-based digital ticketing, the strengthening of multi-channel digital promotions, and the development of a visitor database. This study concluded that the implementation of the Ward and Peppard-based IS/IT strategy could increase the competitiveness of Curug Gomblang, improve service quality, and support more modern and sustainable tourism management.